2018
DOI: 10.1101/333872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does a history of sexual and physical childhood abuse contribute to HIV infection risk in adulthood? A study among post-natal women in Harare, Zimbabwe

Abstract: BackgroundSexual and physical abuse in childhood creates a great health burden including on mental and reproductive health. A possible link between child abuse and HIV infection has increasingly attracted attention. This paper investigated whether a history of child physical and sexual abuse is associated with HIV infection among adult women.MethodsA cross sectional survey was conducted among 2042 postnatal women (mean age=26y) attending six public primary health care clinics in Harare, Zimbabwe within 6 weeks… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Similar studies in Africa have found male dominance and sexual entitlement influencing such relations [37]. Although HIV status is not always related or does not always reach significance levels with violent experiences [38], the fact that having an STI, it being a strong risk factor for HIV shows that sexual factors are strongly related to intimate partner violence [39,40]. STIs which signify non-use of protection during sex illustrate women's failure or inability to negotiate safe sex with their partners due to fear of several things including being blamed by the partner, being rejected or a clear use of male force during sex.…”
Section: Discussionmentioning
confidence: 79%
“…Similar studies in Africa have found male dominance and sexual entitlement influencing such relations [37]. Although HIV status is not always related or does not always reach significance levels with violent experiences [38], the fact that having an STI, it being a strong risk factor for HIV shows that sexual factors are strongly related to intimate partner violence [39,40]. STIs which signify non-use of protection during sex illustrate women's failure or inability to negotiate safe sex with their partners due to fear of several things including being blamed by the partner, being rejected or a clear use of male force during sex.…”
Section: Discussionmentioning
confidence: 79%
“…Findings from this study indicated that being in a monogamous marriage was the only factor associated with the risk of IPV amongst our respondents. In contrast to this finding, the study from Uganda showed that the sociodemographic status of being married was associated with a higher risk of IPV [74], while another type of marital status, such as being divorced, was also associated with IPV in another context [75,76]. This calls for concerted efforts including improving public awareness and providing family counselling aimed at stemming the tide of IPV regardless of marital status and marriage settings.…”
Section: Discussionmentioning
confidence: 84%
“…Anal rape, particularly in children, is associated with a multiplied risk of infection because anal tissues can be easily damaged (Murray, Nguyen, & Cohen, 2014). Victims of sexual violence during childhood are more likely to engage in an array of behaviours later in life that put them at greater risk of HIV acquisition, including substance abuse, homosexuality, having multiple partners, and participating in sex work (Miltz et al., 2019; Mimiaga et al., 2009; Shamu et al., 2019). Furthermore, sexual coercion among adolescents and adults is associated with low self‐esteem and depression, factors that perpetuate many of the risk behaviours for HIV infection (Richter et al., 2014).…”
Section: Discussionmentioning
confidence: 99%